2020
DOI: 10.1038/s41598-020-75698-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale tracking of wild waterfowl and their impact on highly pathogenic avian influenza outbreaks in the Republic of Korea, 2014–2015

Abstract: Wild migratory waterfowl are considered one of the most important reservoirs and long-distance carriers of highly pathogenic avian influenza (HPAI). Our study aimed to explore the spatial and temporal characteristics of wild migratory waterfowl’s wintering habitat in the Republic of Korea (ROK) and to evaluate the impact of these habitats on the risk of HPAI outbreaks in commercial poultry farms. The habitat use of 344 wild migratory waterfowl over four migration cycles was estimated based on tracking records.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Fine-scale tracking of wild migratory birds has revealed that wild birds from Northern Russia, Mongolia, and Siberia migrate to South Korea for the winter [35]. In particular, most return to the western and mid-central provinces of South Korea [36]. This high density of wild birds is associated with a higher incidence of AIVs in poultry farms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine-scale tracking of wild migratory birds has revealed that wild birds from Northern Russia, Mongolia, and Siberia migrate to South Korea for the winter [35]. In particular, most return to the western and mid-central provinces of South Korea [36]. This high density of wild birds is associated with a higher incidence of AIVs in poultry farms.…”
Section: Discussionmentioning
confidence: 99%
“…This high density of wild birds is associated with a higher incidence of AIVs in poultry farms. The risk of HPAI occurrence is 3-8-times higher in poultry farms within waterfowl habitats than in poultry farms outside waterfowl habitats [36]. Therefore, it is important to conduct surveillance of AIVs in wild birds to prevent and/or control outbreaks in poultry farms.…”
Section: Discussionmentioning
confidence: 99%
“…Migratory wild birds play a role of natural reservoirs and spread AI between different territories (Cheon et al., 2018; Gaidet et al., 2010; Lisovski et al., 2018). A recent study reported that poultry farms located within wildfowl habitats were more likely to be infected with HPAI in the ROK (K. Lee et al., 2020). To minimize the risk of HPAIv infection in poultry farms, the animal health authorities could systematically organize wild bird surveillance programmes for HPAIv.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these migratory waterfowl could have contaminated the surrounding areas and caused HPAI outbreaks in the adjacent duck farms. Lee et al [ 29 ] reported that during the HPAI (H5N8) epidemic from 2014 to 2016, an extension of the habitat range of migratory and non-migratory sub-populations of wild migratory waterfowl was related to the highest risk of disease outbreaks. The second phase of the HPAI (H5N8) epidemic began during the autumn migration period of wild migrating waterfowl and resulted in HPAI outbreaks in adjacent duck farms.…”
Section: Discussionmentioning
confidence: 99%